Erythema of Rosacea Affects Health-Related Quality of Life: Results of a Survey Conducted in Collaboration with the National Rosacea Society - Hilary E. Baldwin; Julie Harper; Sarah Baradaran; Vaishali Patel (Adis, Springer Healthcare, 2019)
Abstract Introduction Persistent facial erythema associated with rosacea may negatively impact quality of life (QoL), self-esteem, and self-confidence. We evaluated burden and health-related QoL (HRQoL) impacts of centrofacial erythema of rosacea. Methods A cross-sectional, Web-based survey conducted in collaboration with the National Rosacea Society enrolled adults who self-reported having received a physician diagnosis of rosacea and self-evaluated their current erythema as mild to severe on the validated Subject Self-Assessment for Rosacea Facial Redness. Sociodemographic and clinical characteristics, rosacea symptoms, and their impacts on QoL [validated Impact Assessment for Rosacea Facial Redness (IA-RFR)] and HRQoL [validated Dermatology Life Quality Index (DLQI)] were recorded. Results A total of 708 eligible respondents completed the survey (white/Caucasian, 93.5%; female, 83.1%; mean age, 52.4 years). Respondents had mild (59.2%), moderate (33.2%), or severe (7.6%) erythema. The most bothersome symptoms were persistent facial erythema (69.2%) and blushing/flushing (60.9%). Mean IA-RFR scores showed negative impacts across all severities of erythema. The mean (standard deviation) total DLQI score was 5.2 (6.0) overall [mild erythema, 3.8 (4.9); moderate, 5.7 (5.4); severe, 13.4 (8.9); P < 0.0001]. Conclusion Centrofacial erythema of rosacea represents a substantial HRQoL burden, especially for those with more severe erythema. Funding Allergan plc, Dublin, Ireland.